Evaluasi Kualitas Acara Lomba Karaoke Jepang sebagai Sarana Promosi Budaya Jepang di Palembang - Rahman, Muhammad Arief (Program Studi Sastra Jepang, Universitas Jenderal Soedirman, 2024)
This study aims to evaluate the quality of Japanese Karaoke Competition event as a means of promoting Japanese culture in Palembang. The variables tested in this study were event quality and promotion of Japanese culture. The methodology used was a survey using a questionnaire distributed to 30 respondents who attended the event. The data obtained was then analyzed using descriptive statistical techniques. The results showed that the quality of the event and the promotion of Japanese culture were rated quite good by the respondents, but there are some aspects that need to be improved to improve the quality of the event and the promotion of Japanese culture in Palembang. The implication of this research is that event managers and the promotion of Japanese culture in Palembang need to improve the aspects that need to be improved and increase the promotion of Japanese culture to be more effective in promoting Japanese culture in Palembang.